2022
DOI: 10.52131/pjhss.2022.1004.0314
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative Analysis of the Problems and Prospects of Orphanages in Khyber Pakhtunkhwa, Pakistan

Abstract: A child who loses one or both of his/her parents and does not have any immediate guardian, so they spend their childhood in orphanages. During their stay in orphanages, these children are confronted with numerous issues. This research was conducted at an orphanage center in District Malakand. In order to have a more in-depth understanding of the issue, the researchers employed the Qualitative method in the study. The study adopted a purposive sampling technique for the selection of respondents. Ten respondents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…The findings revealed that orphans face various challenges, including stigma, social isolation, discrimination, food insecurity, sexual abuse, exploitation, and poor health outcomes. The study also proposed intervention strategies to address these issues and protect the well-being of orphans in orphanages 16 . Such children often become soft targets as victims of militancy 17 .…”
Section: Introductionmentioning
confidence: 99%

Honoring the Sacred Duty: Orphan Care in Islam and Pakistan

Hafiz Muhammad Azeem,
Omar Mahmood Wattoo,
Advocate High Court LL.M. LL.B. (hons)
2023
Al-Nasr
“…The findings revealed that orphans face various challenges, including stigma, social isolation, discrimination, food insecurity, sexual abuse, exploitation, and poor health outcomes. The study also proposed intervention strategies to address these issues and protect the well-being of orphans in orphanages 16 . Such children often become soft targets as victims of militancy 17 .…”
Section: Introductionmentioning
confidence: 99%

Honoring the Sacred Duty: Orphan Care in Islam and Pakistan

Hafiz Muhammad Azeem,
Omar Mahmood Wattoo,
Advocate High Court LL.M. LL.B. (hons)
2023
Al-Nasr